Комунікативна толерантність поліцейських у контексті вивчення їх емоційного інтелекту - Євдокімова, О. О.; Yevdokimova, O. O.; Пономаренко, Я. С.; Ponomarenko, Ya. S.; ResearcherID: I-7336-2016; Olena Yevdokimova; Пономаренко (Посохова) Яна Сергіївна (Право і безпека. – 2019. – № 2 (73). – С. 101-108, 2019)
Подано результати емпіричного дослідження особливостей проявів емоційного інтелекту у працівників поліції з різним рівнем комунікативної толерантності на етапі первинної професійної підготовки. Для цього застосовано опитувальник «Загальна комунікативна толерантність» (В. В. Бойко) й тест «Емоційний інтелект» (Д. В. Люсін). Вибірку становили 132 слухачі курсів первинної професійної підготовки поліцейських Харківського національного університету внутрішніх справ. Результати дослідження засвідчили відмінності у показниках емоційного інтелекту у слухачів із різним рівнем комунікативної толерантності. Емпірично доведено, що емоційний інтелект у ситуаціях проблемного спілкування виступає інтегральною особистісною ознакою працівника поліції, яка дозволяє йому успішно розпізнавати й інтерпретувати як власні емоції, так і емоції партнера по спілкуванню.

This paper presents the results of an empirical study of the peculiarities of manifestations of emotional intelligence among police officers with different levels of communicative tolerance at the stage of primary vocational training. In this context, the actual model of emotional intelligence and its practical application need to be verified taking into account the specifics of police activity. Emotional intelligence is considered primarily as an integral feature of the personality of a policeman in the context of his professional communication in situations that are problematic. The emotional intelligence of the individual is represented in the article as a cognitive ability to perceive and analyze both their own and others’ emotional states and emotional manifestations; as well as the ability to correctly regulate and use them. Communicative tolerance, in turn, is one of the most important features of the police officer, which shows his attitude to people, the degree of tolerance to unpleasant or unacceptable, in his opinion, mental states, qualities and deeds. As a psychodiagnostic tool, the questionnaire “General communicative tolerance” (V. V. Boyko) and the “Emotional Intelligence” test (D. V. Lusin) were used. The sample consisted of 132 students of initial training of police officers. The results of the study indicate differences in the manifestations of emotional intelligence in students with different levels of communicative tolerance. It is empirically proven that emotional intelligence in situations of problematic communication acts as an integral personality of the police officer, which allows him to successfully recognize and interpret the emotions of both his own and the communication partner. The study of the level of emotional intelligence of the police at the stage of professional training will allow the psychological support service to better address the tasks of professional selection and psychological support for future policemen.

Представлены результаты эмпирического исследования особенностей проявлений эмоционального интеллекта у работников полиции с разным уровнем коммуникативной толерантности на этапе первичной профессиональной подготовки. Были применены опросник «Общая коммуникативная толерантность» (В. В. Бойко) и тест «Эмоциональный интеллект» (Д. В. Люсин). Выборку составили 132 слушателя курсов первичной профессиональной подготовки полицейских Харьковского национального университета внутренних дел. Результаты исследования засвидетельствовали различия в показателях эмоционального интеллекта у слушателей с разным уровнем коммуникативной толерантности. Эмпирически доказано, что эмоциональный интеллект в ситуациях проблемного общения выступает интегральной личностной характеристикой работника полиции, позволяющей ему успешно распознавать и интерпретировать как собственные эмоции, так и эмоции партнёра по общению.
Коммуникативная толерантность полицейских в контексте изучения их эмоционального интеллекта
Communicative tolerance of policemen in the context of their emotional intelligence’ study
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; комунікативна толерантність; професійне спілкування; емоційний інтелект; професійна підготовка; поліцейський; коммуникативная толерантность; профессиональное общение; эмоциональный интеллект; профессиональная подготовка; полицейский; communicative tolerance; professional communication; emotional intelligence; vocational training; police officers